The Wake at the Root: Understanding Racial Identity Refinement through Genetic Ancestry Testing and Theater Performance - Devin A. Heyward (Societies, 2022)
The racial identity literature has operationalized identity formation as progressive stage models, usually triggered by the experience of a negative race-based event. With the advent of new genealogical technology, it is imperative to include experiences that participants elect to experience (i.e., self-initiated or agentic encounter events). By using this perspective, identity processes become fluid and more expansive. In the context of this study, genetic ancestry tests are operationalized as a self-initiated encounter event. Participants (n = 8) were enrolled in an arts-in-education program that uses theater to explore Black Americans’ identities and family histories. This study used theater performance and modified life narrative interviews to understand how participation informed understandings of the self and others. Subsequent interviews highlighted how participants internalized the genetic test results and their participation within the group. Results indicated that, while participants were deeply invested in learning more about their ancestral roots, there were concerns related to the test results and their meaning for individuals. This study highlights that for the Black diaspora, identity is informed by ancestry and family history, as well as by interactions with created community members. Overall, this study opens the possibility for deeper exploration of racial identity formation within critical social psychology.